Coupling observational methods and the DayCent model to improve examinations of N2O production pathways - Shauna-kay Rainford; Julius C. Havsteen; Joachim Mohn; Christof Ammann; Sonja G. Keel (Nutrient Cycling in Agroecosystems, 2026)
The traditional calibration approach for process-based models, such as DayCent, consists of the iterative adjustment of model parameters and comparison of the simulated total N 2 O flux to measured observations. However, the contributions of individual production pathways, namely nitrification and denitrification, are uncertain. Here, N 2 O emissions from the soil of sugar beet plots with control (Null) and mineral (NPK) fertilizer treatments were measured by a static chamber technique. The isotopic composition of emitted N 2 O was analyzed to identify the N 2 O production pathways. The latter showed that denitrification was the predominant source of N 2 O emissions at this site. The model’s default settings strongly overestimated the contributions of nitrification. This incorrect allocation of N 2 O emissions to nitrification could partly be explained by the model’s tendency to underestimate the soil water content during the growing season. DayCent model parameters were also manually adjusted to better represent the observation derived contributions of nitrification and denitrification. Although, this “expert-informed approach”, showed a slightly lower performance concerning the cumulative N 2 O flux (Null: RMSE = 0.37 kg N ha −1 yr −1 , NPK: RMSE = 0.50 kg N ha −1 yr −1 ) than the traditional calibration (Null: RMSE = 0.15 kg N ha −1 yr −1 , NPK: RMSE = 0.10 kg N ha −1 yr −1 ), it may be considered as more representative because it better reflected the higher contribution from denitrification shown by the isotope data. This study demonstrates that the inclusion of observational methods, such as isotope measurements, can provide important insight into model function and improve pathway-specific estimation of N 2 O emissions in DayCent.

“It’s just not worth it anymore”: A Mixed Methods Study Examining the Impact of Reinstating Reimbursement Tiers in the Child and Adult Care Food Program - Katharina C Fiedler; Kassandra A. Bacon; Danielle L. Lee; Reka Vasicsek; Celeste Felix; Samantha Kay-Daleiden Marshall; Elyse Homel Vitale; Susana L. Matias; Lorrene D. Ritchie (Journal of Nutrition Education and Behavior, 2026)

Using Drone‐Derived Imagery to Describe Prey Sharing Behaviors in Two Piscivorous Resident Killer Whale Populations - Sharon W. C. Kay; Lance G. Barrett‐Lennard; Brittany C. Visona‐Kelly; Marie‐Ana Mikus; Michael N. Weiss; Darren P. Croft; Valeria Vergara; Holly Fearnbach; John W. Durban; Chris T. Darimont (Marine Mammal Science, 2026)
Cooperative foraging occurs across diverse taxa and facilitates prey acquisition and social learning, particularly when prey is shared among group members. In Resident killer whales ( Orcinus orca ater ), prey sharing is central to how individuals acquire salmonid prey, yet current research has relied primarily on boat‐based observations. Using 10 years of drone‐based imagery, we examined prey sharing behaviors in two populations, endangered Southern Resident killer whales (SRKWs) and threatened Northern Resident killer whales (NRKWs). Our goal was to evaluate the utility of drones for documenting prey sharing behaviors and conduct preliminary comparisons between NRKW and SRKWs. We detected 41 NRKW and 52 SRKW predation events, with prey sharing observed in 24 NRKW (59%) and 22 SRKW (42%) events. Drones effectively documented prey sharing at or near the surface, revealing subtle behaviors and allowing us to track the roles of individuals. Initial comparisons revealed that adult female NRKWs shared prey more frequently than adult female SRKWs and shared larger portions of prey. Although preliminary, our findings suggest differences in prey sharing between the populations, possibly reflecting social or ecological differences. Overall, drone‐based methods provide valuable insights into foraging behavior in free‐ranging cetaceans and offer a new approach to investigate cooperative behaviors.

Associations of cardiorespiratory fitness with structural brain networks in ageing: insights from The Maastricht Study - Kristina Ukropcova; Kay Deckers; Annemarie Koster; Joost J. A. de Jong; Jacobus F. A. Jansen; Walter H. Backes; Hans H. C. M. Savelberg; Carla van der Kallen; Miranda T. Schram; Sebastian Köhler; Veerle van Gils (GeroScience, 2026)

Development and Application of the Paced Bottle-Feeding Checklist - Taylor N. Richardson; Melissa C. Kay; Alison K. Ventura (Journal of Nutrition Education and Behavior, 2026)

The effects of simultaneous isometric and eccentric- or concentric-biased exercise on cardiovascular and muscular health of young individuals - A. W. Baross; B. H. Wright; D. A. Langdon; A. D. Kay; M. Cauchi; A. Clarke; B. Pitham; C. Willmont; T. Barnett; C. Key; M. Reynolds; A. Thomas; et al. (European Journal of Applied Physiology, 2026)

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

The Interplay of Traits, Phylogeny and Abundance Shapes Spatial Mammal Diversity Patterns - Kay Zin Than; Alice C. Hughes; Lin Wang; Zaw Zaw; Rui‐Chang Quan (Global Ecology and Biogeography, 2025)
Aim Terrestrial mammal communities are crucial indicators of tropical ecosystem health and sustainability. However, the role of shared species responses driven by functional traits and phylogenetic relatedness in shaping community assembly remains underexplored for identifying conservation hotspots. Spatial predictions of species diversity also remain limited by approaches that fail to jointly account for species occupancy and abundance. This study evaluates trait‐ and phylogeny‐informed environmental filtering in structuring mammal communities and maps spatial diversity patterns by integrating species occupancy and abundance across spatial–temporal scales. Ultimately, areas of high mammal diversity reflecting underlying assembly processes are identified to guide regional conservation planning. Location Myanmar and China. Time Period 2015–2021. Major Taxa Studied Terrestrial mammals. Methods We deployed 936 camera traps over 6 years across Upper Myanmar and Xishuangbanna, China, using a nested sampling design that ensured robust spatial–temporal replication, and analysed the data using community hierarchical models. Results Climate and habitat factors predominantly drive species richness, while traits and phylogenetic relatedness jointly shape distinct community patterns. Seasonal variation in local diversity underscores the role of environmental filtering in structuring mammal communities across space and time. Large‐bodied omnivores favour stable temperature niches, whereas reduced precipitation filters communities towards wide‐ranging mammals. Anthropogenic disturbances and forest cover loss alter community structure, diminishing the prevalence of carnivorous traits. Predictive community maps with uncertainty estimates guide future survey efforts through a more integrative, data‐informed approach to regional planning. Main Conclusions This study presents a novel framework for improving climate‐ and habitat‐based biodiversity models by integrating trait‐ and phylogeny‐informed assembly processes with abundance‐based predictions across suitable habitats. The findings, including phylogenetically clustered niches in Cervidae and Felidae, suggest that shared evolutionary adaptations, such as temperature tolerance in ungulates and disturbance tolerance in carnivores, shape community assembly under varying environmental pressures and can inform spatial conservation prioritisation.

Current Views on Addressing Nutritional Concerns in Adult Cystic Fibrosis Patients from Practicing Registered Dietitians - C. West; M. Kay; P. Davidson; L. Wright; C. Colin (Journal of the Academy of Nutrition and Dietetics, 2025)

Novel Correlations Between Lung Function and Gut Microbial-Produced VOCs in the Exhaled Breath of Ultramarathon Runners: Insights from the 2019 Ultra-Trail du Mont Blanc - Hsuan Chou; Amy Craster; Kayleigh Arthur; Billy Boyle; Max Allsworth; Eli F. Kelley; Glenn M. Stewart; Courtney M. Wheatley-Guy; Jesse Schwartz; Caitlin C. Fermoyle; Briana L. Ziegler; Kay A. Johnson; et al. (Journal of Science in Sport and Exercise, 2025)

A Multimedia Arsenic Exposure Assessment for the Hopi Tribe, AZ, USA - Adam C. Carl; Robert A. Canales; Jonathan E. Blohm; Lorencita Joshweseoma; Steven J. Hadeed; Jefferey L. Burgess; Robin B. Harris; Mary Kay O’Rourke (Exposure and Health, 2025)

Measuring Dietary Quality Among Toddlers in the Feeding Infants and Toddlers Study, 2016, Using the New Healthy Eating Index-Toddlers-2020 - Melissa C. Kay; Joel Hampton; Susan Pac; Lyndsey Huss; Alison L. Eldridge (Journal of the Academy of Nutrition and Dietetics, 2025)

Spray-flame synthesis of LaCo0.2Mn0.8O3 for selective peroxymonosulfate activation into singlet oxygen towards efficient degradation of carbamazepine - Mohaned Hammad; Steven Angel; Ahmed K. Al-kamal; Anam Asghar; Mena-Alexander Kräenbring; Adil Amin; Haakon T.A. Wiedemann; Amin S. Amin; Vineetha Vinayakumar; Torsten C. Schmidt; Christopher W.M. Kay; Doris Segets; et al. (Process Safety and Environmental Protection, 2025)

Robotic technologies for in-orbit assembly of a large aperture space telescope: A review - Manu H. Nair; Mini C. Rai; Mithun Poozhiyil; Steve Eckersley; Steven Kay; Joaquin Estremera (Advances in Space Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sea ice-melt amount estimated from spring hydrography in the Sea of Okhotsk: spatial and interannual variabilities - Mariko Honda; Kay I. Ohshima; Vigan Mensah; Jun Nishioka; Masatoshi Sato; Stephen C. Riser (Journal of Oceanography, 2024)
This study provides the first estimation of sea ice-melt amount in the Sea of Okhotsk based on spring hydrographic data accumulated for nearly a hundred years. Just after sea ice melts completely, a low-salinity layer appears on the ocean surface, overlying the layer of Winter Water at the freezing point. The integration of the salinity decrease from Winter Water should correspond to the total ice-melt amount. We developed an algorithm to extract the profiles that clearly show the salinity deficit and converted the salinity deficit to the ice-melt amount from all available data. The climatological map shows that ice-melt amount decreases toward the ice edge and exhibits large values around the northern Sakhalin Island, reflecting the ice thickness distribution. In the southern area (south of 48°N), where sea ice is transported from the north, the average ice-melt amount is estimated to be ~ 71 cm in thickness. It is clearly shown that the ice-melt amount has decreased by ~ 30% in the southern area since the 1990s. These changes possibly affect the regional climate through the decreased latent heat of sea ice and potentially affect biological production through weakened stratification caused by decreased ice melt. We also suggested that ice-melt amount did not show a significant trend during the 1930s–1970s, implying that our methodology could extract information on sea ice before the era of satellite observations.

Lower crustal control in the iron isotope systematics of plutonic xenoliths from Adak Island, Central Aleutians, with implications for arc magma geochemistry - Emma S. Sosa; Claire E. Bucholz; Juan David Hernández-Montenegro; Michael A. Kipp; François L.H. Tissot; Barbara C. Ratschbacher; Jennifer M. Jackson; Suzanne Mahlburg Kay; Robert W. Kay (Geochimica et Cosmochimica Acta, 2024)

Awareness and Support of Responsive Bottle Feeding Among WIC Counselors and Caregivers: A Formative Qualitative Study - Taylor N. Richardson; Alison K. Ventura; Ashley Brewer; Avan Shirwani; Belen de la Barrera; Melissa C. Kay (Journal of Nutrition Education and Behavior, 2024)

Concordance in dietary intake among caregivers and infants during the period of complementary feeding: A scoping review - Sara V. Bernate Angulo; Brooke T. Nezami; Stephanie L. Martin; Melissa C. Kay; Taylor N. Richardson; Heather M. Wasser (Appetite, 2024)

The multiview observatory for solar terrestrial science (MOST) - N. Gopalswamy; S. Christe; S.F. Fung; Q. Gong; J.R. Gruesbeck; L.K. Jian; S.G. Kanekal; C. Kay; T.A. Kucera; J.E. Leake; L. Li; P. Mӓkelӓ; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Biodiversity conservation in Myanmar's coastal wetlands: Focusing on saltwater crocodile habitats and connectivity - Kay Zin Than; Zaw Zaw; Rui-Chang Quan; Alice C. Hughes (Biological Conservation, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Ambient air particulate total lung deposited surface area (LDSA) levels in urban Europe - Xiansheng Liu; Hadiatullah Hadiatullah; Xun Zhang; Pedro Trechera; Marjan Savadkoohi; Meritxell Garcia-Marlès; Cristina Reche; Noemí Pérez; David C.S. Beddows; Imre Salma; Wanda Thén; Panayiotis Kalkavouras; et al. (Science of The Total Environment, 2023)

Active debris removal: A review and case study on LEOPARD Phase 0-A mission - Mithun Poozhiyil; Manu H. Nair; Mini C. Rai; Alexander Hall; Connor Meringolo; Mark Shilton; Steven Kay; Danilo Forte; Martin Sweeting; Nikki Antoniou; Victoria Irwin (Advances in Space Research, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Patterns of microparticles in blank samples: A study to inform best practices for microplastic analysis - Keenan Munno; Amy L. Lusher; Elizabeth C. Minor; Andrew Gray; Kay Ho; Jeanne Hankett; Chih-Fen T Lee; Sebastian Primpke; Rachel E. McNeish; Charles S. Wong; Chelsea Rochman (Chemosphere, 2023)

Impact of Access and Benefit Sharing implementation on biological control genetic resources - Peter G. Mason; Barbara I. P. Barratt; Fernando Mc Kay; Johannette N. Klapwijk; Luciana C. Silvestri; Martin Hill; Hariet L. Hinz; Andy Sheppard; Jacques Brodeur; Marcello Diniz Vitorino; Philip Weyl; Kim A. Hoelmer (BioControl, 2023)
The third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the use of genetic resources was further developed when the Nagoya Protocol on Access and Benefit Sharing came into effect in 2014. Interpretation of how this agreement is being implemented is wide-ranging and there are implications for biological control. A survey of biological control workers indicated that while some countries have facilitated access to biological control genetic resources, requirements in other countries have impeded biological control implementation. There was consensus that benefits to provider countries should be in the form of supporting local research communities. There was also agreement that the free use and exchange of biological control genetic resources has provided benefits to the global community, including to both providers and recipients of the agents. It is recommended that consideration of the free use and exchange principal should be a key element of Access and Benefit Sharing measures for the future.

International agreement for the use and exchange of classical biological control genetic resources: a practical proposal - Peter G. Mason; Fernando Mc Kay; Luciana C. Silvestri; Martin Hill; Philip Weyl; Hariet L. Hinz; Jacques Brodeur; Marcelo Diniz Vitorino; Barbara I. P. Barratt (BioControl, 2023)
The Nagoya Protocol on Access and Benefit Sharing (ABS) was implemented to further develop the third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the utilization of genetic resources. Interpretation of this agreement is wide-ranging and there is concern that if ABS measures are poorly implemented biological control and the resultant public good will be greatly impeded. The ethos of multilateral use and exchange of genetic resources used in classical biological control will be particularly affected. In the spirit of the fair and equitable sharing of benefits arising out of the utilization of genetic resources, we propose a simple practical solution in the form of an international agreement on the use and exchange of classical biological control genetic resources.

Projected effects of climate change on marine ecosystems in Southeast Asian seas - Susan Kay; Arlene L. Avillanosa; Victoria V. Cheung; Hung N. Dao; Benjamin Jareta Gonzales; Herminie P. Palla; Radisti A. Praptiwi; Ana M. Queirós; Sévrine F. Sailley; Joel D. C. Sumeldan; Wan Mohd Syazwan; Amy Yee-Hui Then; et al. (Frontiers in Marine Science, 2023)
The seas of Southeast Asia are home to some of the world’s most diverse ecosystems and resources that support the livelihoods of millions of people. Climate change will bring temperature changes, acidification and other environmental change, with uncertain consequences for human and natural systems, but there has been little regional-scale climate modelling of the marine ecosystem. We present initial dynamically downscaled projections using a biogeochemical model suitable for coastal and shelf seas. A coupled physical-biogeochemical model with a resolution of 0.1° (approximately 11 km) was used to create projections of future environmental conditions under moderate (RCP4.5) and high (RCP8.5) greenhouse gas scenarios. Changes for different parts of the region are presented, including four sensitive coastal sites of key importance for biodiversity and sustainable development: UNESCO Biosphere Reserves at Cu Lao Cham-Hoi An in Vietnam, Palawan in the Philippines and Taka Bonerate-Kepulauan Selayar in Indonesia, and coastal waters of Sabah, Malaysia, which include several marine parks. The projections show a sea that is warming by 1.1 to 2.9°C through the 21st century, with dissolved oxygen decreasing by 5 to 13 mmol m -3 and changes in many other environmental variables. The changes reach all parts of the water column and many places are projected to experience conditions well outside the range seen at the start of the century. The resulting damage to coral reefs and altered species distribution would have consequences for biodiversity, the livelihoods of small-scale fishers and the food security of coastal communities. Further work using a range of global models and regional models with different biogeochemical components is needed to provide confidence levels, and we suggest some ways forward. Projections of this type serve as a key tool for communities and policymakers as they plan how they will adapt to the challenge of climate change.

Synthesis of novel LaCoO3/graphene catalysts as highly efficient peroxymonosulfate activator for the degradation of organic pollutants - Mohaned Hammad; Steven Angel; Ahmed K. Al-Kamal; Anam Asghar; Amin Said Amin; Mena-Alexander Kräenbring; Haakon T.A. Wiedemann; Vineetha Vinayakumar; Md Yusuf Ali; Paolo Fortugno; Cheolyong Kim; Torsten C. Schmidt; et al. (Chemical Engineering Journal, 2023)

Adoptees’ views and experiences of direct-to-consumer (DTC) genomic testing: an exploratory interview study from the UK - Alison C. Kay; Nicola V. Taverner (Journal of Community Genetics, 2022)
Direct-to-consumer (DTC) genomic testing for ancestry and health may appeal to adoptees looking to fill gaps in their family information. There are only a handful of published studies on adoptees’ views and experiences of DTC testing and none of these is from the UK. The recent UK House of Commons Science and Technology Committee report (GB Parliament, House of Commons 2021) did not address the gains or challenges for adopted people specifically, although the Committee did consider that robust evidence of opportunities or risks for any user of a DTC testing kit is limited. In this study presented here, semi-structured interviews were conducted with ten UK adult adoptees recruited via social media. Reflexive thematic analysis (Braun and Clarke 2006, 2019) of the interview transcripts identified three main themes: Decisional influencers of longing, uncertainty and normalisation of DNA kit use; Informational drivers to gain clarity but avoid new worrisome information; and talk around Negotiating Visibility to birth family and commercial third parties. A further theme of Meaning Making related to adoptees’ views of testing outcomes as bringing feelings of resolution or discordance. This study identified many challenging deliberations for adoptees in evaluating whether to take a DTC test and what to do when their results were returned. Additionally, adoptees’ consideration of data privacy issues appears hampered by already having shared identifying information about themselves in their wider adoptee search. Further research is encouraged.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantifying cancer risk from exposures to medical imaging in the Risk of Pediatric and Adolescent Cancer Associated with Medical Imaging (RIC) Study: research methods and cohort profile - Marilyn L. Kwan; Diana L. Miglioretti; Erin J. A. Bowles; Sheila Weinmann; Robert T. Greenlee; Natasha K. Stout; Alanna Kulchak Rahm; Susan A. Alber; Priscila Pequeno; Lisa M. Moy; Carly Stewart; Cindy Fong; et al. (Cancer Causes & Control, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Human cytomegalovirus multiple-strain infections and viral population diversity in haematopoietic stem cell transplant recipients analysed by high-throughput sequencing - A. Dhingra; J. Götting; P. R. Varanasi; L. Steinbrueck; S. Camiolo; J. Zischke; A. Heim; T. F. Schulz; E. M. Weissinger; P. C. Kay-Fedorov; A. J. Davison; N. M. Suárez; et al. (Medical Microbiology and Immunology, 2021)
Human cytomegalovirus (HCMV) is an important opportunistic pathogen in allogeneic haematopoietic stem cell transplant (HSCT) recipients. High-throughput sequencing of target-enriched libraries was performed to characterise the diversity of HCMV strains present in this high-risk group. Forty-four HCMV-DNA-positive plasma specimens (median viral input load 321 IU per library) collected at defined time points from 23 HSCT recipients within 80 days of transplantation were sequenced. The genotype distribution for 12 hypervariable HCMV genes and the number of HCMV strains present (i.e. single- vs. multiple-strain infection) were determined for 29 samples from 16 recipients. Multiple-strain infection was observed in seven of these 16 recipients, and five of these seven recipients had the donor (D)/recipient (R) HCMV-serostatus combination D + R + . A very broad range of genotypes was detected, with an intrahost composition that was generally stable over time. Multiple-strain infection was not associated with particular virological or clinical features, such as altered levels or duration of antigenaemia, development of acute graft-versus-host disease or increased mortality. In conclusion, despite relatively low viral plasma loads, a high frequency of multiple-strain HCMV infection and a high strain complexity were demonstrated in systematically collected clinical samples from this cohort early after HSCT. However, robust evaluation of the pathogenic role of intrahost viral diversity and multiple-strain infection will require studies enrolling larger numbers of recipients.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Bright spots as climate‐smart marine spatial planning tools for conservation and blue growth - Ana M. Queirós; Elizabeth Talbot; Nicola J. Beaumont; Paul J. Somerfield; Susan Kay; Christine Pascoe; Simon Dedman; Jose A. Fernandes; Alexander Jueterbock; Peter I. Miller; Sevrine F. Sailley; Gianluca Sará; et al. (Global Change Biology, 2021)
Marine spatial planning that addresses ocean climate‐driven change (‘climate‐smart MSP’) is a global aspiration to support economic growth, food security and ecosystem sustainability. Ocean climate change (‘CC’) modelling may become a key decision‐support tool for MSP, but traditional modelling analysis and communication challenges prevent their broad uptake. We employed MSP‐specific ocean climate modelling analyses to inform a real‐life MSP process; addressing how nature conservation and fisheries could be adapted to CC. We found that the currently planned distribution of these activities may become unsustainable during the policy's implementation due to CC, leading to a shortfall in its sustainability and blue growth targets. Significant, climate‐driven ecosystem‐level shifts in ocean components underpinning designated sites and fishing activity were estimated, reflecting different magnitudes of shifts in benthic versus pelagic, and inshore versus offshore habitats. Supporting adaptation, we then identified: CC refugia (areas where the ecosystem remains within the boundaries of its present state); CC hotspots (where climate drives the ecosystem towards a new state, inconsistent with each sectors’ present use distribution); and for the first time, identified bright spots (areas where oceanographic processes drive range expansion opportunities that may support sustainable growth in the medium term). We thus create the means to: identify where sector‐relevant ecosystem change is attributable to CC; incorporate resilient delivery of conservation and sustainable ecosystem management aims into MSP; and to harness opportunities for blue growth where they exist. Capturing CC bright spots alongside refugia within protected areas may present important opportunities to meet sustainability targets while helping support the fishing sector in a changing climate. By capitalizing on the natural distribution of climate resilience within ocean ecosystems, such climate‐adaptive spatial management strategies could be seen as nature‐based solutions to limit the impact of CC on ocean ecosystems and dependent blue economy sectors, paving the way for climate‐smart MSP.

Plastic Pollution and Small Juvenile Marine Turtles: A Potential Evolutionary Trap - Emily M. Duncan; Annette C. Broderick; Kay Critchell; Tamara S. Galloway; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; David Santillo; Anton D. Tucker; Scott Whiting; Erina J. Young; Brendan J. Godley (Frontiers in Marine Science, 2021)
The ingestion of plastic by marine turtles is now reported for all species. Small juvenile turtles (including post-hatchling and oceanic juveniles) are thought to be most at risk, due to feeding preferences and overlap with areas of high plastic abundance. Their remote and dispersed life stage, however, results in limited access and assessments. Here, stranded and bycaught specimens from Queensland Australia, Pacific Ocean (PO; n = 65; 1993–2019) and Western Australia, Indian Ocean (IO; n = 56; 2015–2019) provide a unique opportunity to assess the extent of plastic (> 1mm) ingestion in five species [green ( Chelonia mydas ), loggerhead ( Caretta caretta ), hawksbill ( Eretmochelys imbricata ), olive ridley ( Lepidochelys olivacea ), and flatback turtles ( Natator depressus )]. In the Pacific Ocean, high incidence of ingestion occurred in green (83%; n = 36), loggerhead (86%; n = 7), flatback (80%; n = 10) and olive ridley turtles (29%; n = 7). There was an overall lower incidence in IO; highest being in the flatback (28%; n = 18), the loggerhead (21%; n = 14) and green (9%; n = 22). No macroplastic debris ingestion was documented for hawksbill turtles in either site although sample sizes were smaller for this species (PO n = 5; IO n = 2). In the Pacific Ocean, the majority of ingested debris was made up of hard fragments (mean of all species 52%; species averages 46–97%), whereas for the Indian Ocean these were filamentous plastics (52%; 43–77%). The most abundant colour for both sites across all species was clear (PO: 36%; IO: 39%), followed by white for PO (36%) then green and blue for IO (16%; 16%). The polymers most commonly ingested by turtles in both oceans were polyethylene (PE; PO-58%; IO-39%) and polypropylene (PP; PO-20.2%; IO-23.5%). We frame the high occurrence of ingested plastic present in this marine turtle life stage as a potential evolutionary trap as they undertake their development in what are now some of the most polluted areas of the global oceans.

Soil fungal mycelia have unexpectedly flexible stoichiometric C:N and C:P ratios - Tessa Camenzind; Kay Philipp Grenz; Johannes Lehmann; Matthias C. Rillig (Ecology Letters, 2021)
Soil ecological stoichiometry provides powerful theories to integrate the complex interplay of element cycling and microbial communities into biogeochemical models. One essential assumption is that microbes maintain stable C:N:P (carbon:nitrogen:phosphorus) ratios independent of resource supply, although such homeostatic regulations have rarely been assessed in individual microorganisms. Here, we report an unexpected high flexibility in C:N and C:P values of saprobic fungi along nutrient supply gradients, overall ranging between 7‐126 and 20‐1488, respectively, questioning microbial homeostasis. Fungal N:P varied comparatively less due to simultaneous reductions in mycelial N and P contents. As a mechanism, internal recycling processes during mycelial growth and an overall reduced N and P uptake appear more relevant than element storage. The relationships among fungal stoichiometry and growth disappeared in more complex media. These findings affect our interpretation of stoichiometric imbalances among microbes and soils and are highly relevant for developing microbial soil organic carbon and nitrogen models.

The Possession of Coccoliths Fails to Deter Microzooplankton Grazers - Kyle M. J. Mayers; Alex J. Poulton; Kay Bidle; Kimberlee Thamatrakoln; Brittany Schieler; Sarah L. C. Giering; Seona R. Wells; Glen A. Tarran; Dan Mayor; Matthew Johnson; Ulf Riebesell; Aud Larsen; et al. (Frontiers in Marine Science, 2020)
Phytoplankton play a central role in the regulation of global carbon and nutrient cycles, forming the basis of the marine food webs. A group of biogeochemically important phytoplankton, the coccolithophores, produce calcium carbonate scales that have been hypothesized to deter or reduce grazing by microzooplankton. Here, a meta-analysis of mesocosm-based experiments demonstrates that calcification of the cosmopolitan coccolithophore, Emiliania huxleyi , fails to deter microzooplankton grazing. The median grazing to growth ratio for E. huxleyi (0.56 ± 0.40) was not significantly different among non-calcified nano- or picoeukaryotes (0.71 ± 0.31 and 0.55 ± 0.34, respectively). Additionally, the environmental concentration of E. huxleyi did not drive preferential grazing of non-calcified groups. These results strongly suggest that the possession of coccoliths does not provide E. huxleyi effective protection from microzooplankton grazing. Such indiscriminate consumption has implications for the dissolution and fate of CaCO 3 in the ocean, and the evolution of coccoliths.

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Patient attitudes towards brain donation across both neurodegenerative and non-neurodegenerative neurological disorders - Reudi J. W. Chan; Sherilyn Seah; Joel Y. J. Foo; Alisa C. W. Yong; Nicole S. Y. Chia; Sherwin J. U. Agustin; Shermyn X. M. Neo; Kay-Yaw Tay; Wing-Lok Au; Louis C. S. Tan; Adeline S. L. Ng (Cell and Tissue Banking, 2020)

Attitudes of Asian Parkinson patients towards brain donation - Shazma Khan; Joel Y. J. Foo; Nicole S. Y. Chia; Sherwin J. U. Agustin; Shermyn X. M. Neo; Kay-Yaw Tay; Wing-Lok Au; Adeline S. L. Ng; Louis C. S. Tan (Cell and Tissue Banking, 2019)

Coastal Armoring and Sea Turtles: Beachfront Homeowners’ Opinions and Intent - Melissa K. Hill; Martha C. Monroe; Thomas T. Ankersen; Raymond R. Carthy; Tom A. Kay (Coastal Management, 2019)

National-scale analysis of future river flow and soil moisture droughts: potential changes in drought characteristics - Alison C. Rudd; A. L. Kay; V. A. Bell (Climatic Change, 2019)

Early life social and ecological determinants of global DNA methylation in wild spotted hyenas - Zachary M. Laubach; Christopher D. Faulk; Dana C. Dolinoy; Luke Montrose; Tamara R. Jones; Donna Ray; Malit O. Pioon; Kay E. Holekamp (Molecular Ecology, 2019)
Environmental factors early in life can have lasting influence on the development and phenotypes of animals, but the underlying molecular modifications remain poorly understood. We examined cross‐sectional associations among early life socioecological factors and global DNA methylation in 293 wild spotted hyenas ( Crocuta crocuta ) in the Masai Mara National Reserve, Kenya, grouped according to three age classes (cub, subadult and adult). Explanatory variables of interest included annual maternal rank based on outcomes of dyadic agonistic interactions, litter size, wild ungulate prey density and anthropogenic disturbance in the year each hyena was born based on counts of illegal livestock in the Reserve. The dependent variable of interest was global DNA methylation, assessed via the LUminometric Methylation Assay, which provides a percentage methylation value calculated at CCGG sites across the genome. Among cubs, we observed approximately 2.75% higher CCGG methylation in offspring born to high‐ than low‐ranking mothers. Among cubs and subadults, higher anthropogenic disturbance corresponded with greater %CCGG methylation. In both cubs and adults, we found an inverse association between prey density measured before a hyena was 3 months old and %CCGG methylation. Our results suggest that maternal rank, anthropogenic disturbance and prey availability early in life are associated with later life global DNA methylation. Future studies are required to understand the extent to which these DNA methylation patterns relate to adult phenotypes and fitness outcomes.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Partial congruence in habitat patterns for taxonomic and functional diversity of fish assemblages in seagrass ecosystems - Melisa C. Wong; Lauren M. Kay (Marine Biology, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Trapping of lead (Pb) by corn and pea root border cells - David A. Huskey; Gilberto Curlango-Rivera; Robert A. Root; Fushi Wen; Mary Kay Amistadi; Jon Chorover; Martha C. Hawes (Plant and Soil, 2018)

Literature review: dermal monitoring data for pesticide exposure assessment of farm workers - Nichole A. Garzia; John J. Spinelli; Carolyn C. Gotay; Kay Teschke (Journal of Agromedicine, 2018)

National-scale analysis of low flow frequency: historical trends and potential future changes - A. L. Kay; V. A. Bell; B. P. Guillod; R. G. Jones; A. C. Rudd (Climatic Change, 2018)

Exome sequence genotype imputation in globally diverse hexaploid wheat accessions - Fan Shi; Josquin Tibbits; Raj K. Pasam; Pippa Kay; Debbie Wong; Joanna Petkowski; Kerrie L. Forrest; Ben J. Hayes; Alina Akhunova; John Davies; Steven Webb; German C. Spangenberg; et al. (Theoretical and Applied Genetics, 2017)

High‐resolution sequencing reveals unexplored archaeal diversity in freshwater wetland soils - Adrienne B. Narrowe; Jordan C. Angle; Rebecca A. Daly; Kay C. Stefanik; Kelly C. Wrighton; Christopher S. Miller (Environmental Microbiology, 2017)
Summary Despite being key contributors to biogeochemical processes, archaea are frequently outnumbered by bacteria, and consequently are underrepresented in combined molecular surveys. Here, we demonstrate an approach to concurrently survey the archaea alongside the bacteria with high‐resolution 16S rRNA gene sequencing, linking these community data to geochemical parameters. We applied this integrated analysis to hydric soils sampled across a model methane‐emitting freshwater wetland. Geochemical profiles, archaeal communities, and bacterial communities were independently correlated with soil depth and water cover. Centimeters of soil depth and corresponding geochemical shifts consistently affected microbial community structure more than hundreds of meters of lateral distance. Methanogens with diverse metabolisms were detected across the wetland, but displayed surprising OTU‐level partitioning by depth. Candidatus Methanoperedens spp. archaea thought to perform anaerobic oxidation of methane linked to iron reduction were abundant. Domain‐specific sequencing also revealed unexpectedly diverse non‐methane‐cycling archaeal members. OTUs within the underexplored Woesearchaeota and Bathyarchaeota were prevalent across the wetland, with subgroups and individual OTUs exhibiting distinct occupancy and abundance distributions aligned with environmental gradients. This study adds to our understanding of ecological range for key archaeal taxa in a model freshwater wetland, and links these taxa and individual OTUs to hypotheses about processes governing biogeochemical cycling.

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Copy-number variant analysis of classic heterotaxy highlights the importance of body patterning pathways - Erin M. Hagen; Robert J. Sicko; Denise M. Kay; Shannon L. Rigler; Aggeliki Dimopoulos; Shabbir Ahmad; Margaret H. Doleman; Ruzong Fan; Paul A. Romitti; Marilyn L. Browne; Michele Caggana; Lawrence C. Brody; et al. (Human Genetics, 2016)

Solutions for ecosystem‐level protection of ocean systems under climate change - Ana M. Queirós; Klaus B. Huebert; Friedemann Keyl; Jose A. Fernandes; Willem Stolte; Marie Maar; Susan Kay; Miranda C. Jones; Katell G. Hamon; Gerrit Hendriksen; Youen Vermard; Paul Marchal; et al. (Global Change Biology, 2016)
The Paris Conference of Parties ( COP 21) agreement renewed momentum for action against climate change, creating the space for solutions for conservation of the ocean addressing two of its largest threats: climate change and ocean acidification ( CCOA ). Recent arguments that ocean policies disregard a mature conservation research field and that protected areas cannot address climate change may be oversimplistic at this time when dynamic solutions for the management of changing oceans are needed. We propose a novel approach, based on spatial meta‐analysis of climate impact models, to improve the positioning of marine protected areas to limit CCOA impacts. We do this by estimating the vulnerability of ocean ecosystems to CCOA in a spatially explicit manner and then co‐mapping human activities such as the placement of renewable energy developments and the distribution of marine protected areas. We test this approach in the NE Atlantic considering also how CCOA impacts the base of the food web which supports protected species, an aspect often neglected in conservation studies. We found that, in this case, current regional conservation plans protect areas with low ecosystem‐level vulnerability to CCOA , but disregard how species may redistribute to new, suitable and productive habitats. Under current plans, these areas remain open to commercial extraction and other uses. Here, and worldwide, ocean conservation strategies under CCOA must recognize the long‐term importance of these habitat refuges, and studies such as this one are needed to identify them. Protecting these areas creates adaptive, climate‐ready and ecosystem‐level policy options for conservation, suitable for changing oceans.

Evidence for extensive but variable nutrient limitation in New Zealand lakes - Amy C. Krist; Adam D. Kay; Elizabeth Scherber; Katelyn Larkin; Bennett J. Brown; Diana Lu; Donald T. Warren; Ruth Riedl; Maurine Neiman (Evolutionary Ecology, 2016)

A non-canonical role for desmoglein-2 in endothelial cells: implications for neoangiogenesis - Lisa M. Ebert; Lih Y. Tan; M. Zahied Johan; Kay Khine Myo Min; Michaelia P. Cockshell; Kate A. Parham; Kelly L. Betterman; Paceman Szeto; Samantha Boyle; Lokugan Silva; Angela Peng; YouFang Zhang; et al. (Angiogenesis, 2016)

Identification of hydrochemical facies in the Roswell Artesian Basin, New Mexico (USA), using graphical and statistical methods - Brent D. Newman; Kay C. Havenor; Patrick Longmire (Hydrogeology Journal, 2016)

The self‐organising of youth volunteers during the Rena oil spill in New Zealand - Sarah Lockwood; C Kay Weaver; Debashish Munshi; Mary Simpson (New Zealand Journal of Marine and Freshwater Research, 2016)
This study explores the communication and organising of youth volunteers during a crisis, focusing on how they conceived, framed, and executed self‐organising efforts during the 2011 Rena oil spill in New Zealand. It offers insights into the intersections of self‐organising, youth volunteering and crisis events which have not been researched before. The study addresses two core research questions: 1. how was ‘volunteering’ conceptualised by youth volunteers involved in the Rena crisis; and 2. how did these volunteers communicate and self‐organise during this crisis? The findings indicate that self‐organising emerged out of a resistance towards structured responses and as a reaction to the inability of the official volunteer response to meet the needs of the community. Self‐organised efforts were particularly attractive among youth volunteers because they offered flexibility, required minimal administrative processes, and fostered an environment of innovation and creativity. The volunteers’ youthful energy and technological aptitude additionally drove their self‐organised responses. The study identifies the considerable challenges that crisis officials faced in utilising youth volunteers despite the significant advantages of self‐organising.

Use of very high resolution climate model data for hydrological modelling: baseline performance and future flood changes - A. L. Kay; A. C. Rudd; H. N. Davies; E. J. Kendon; R. G. Jones (Climatic Change, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

BCL2 protein signalling determines acute responses to neoadjuvant chemoradiotherapy in rectal cancer - L. Flanagan; A. U. Lindner; C. de Chaumont; J. Kehoe; J. Fay; O. Bacon; S. Toomey; H. J. Huber; B. T. Hennessy; E. W. Kay; D. A. McNamara; J. H. M. Prehn (Journal of Molecular Medicine, 2015)

Probabilistic impacts of climate change on flood frequency using response surfaces I: England and Wales - A. L. Kay; S. M. Crooks; H. N. Davies; C. Prudhomme; N. S. Reynard (Regional Environmental Change, 2014)

Dietary intake of acrylamide and esophageal cancer risk in the European Prospective Investigation into Cancer and Nutrition cohort - Leila Lujan-Barroso; Carlos Alberto González; Nadia Slimani; Mireia Obón-Santacana; Pietro Ferrari; Heinz Freisling; Kim Overvad; Françoise Clavel-Chapelon; Marie-Christine Boutron-Ruault; Antoine Racine; Verena Katzke; Tilman Kühn; et al. (Cancer Causes & Control, 2014)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Characterization of water and wildlife strains as a subgroup of C ampylobacter jejuni using DNA microarrays - Richard A. Stabler; Jonas T. Larsson; Suaad Al‐Jaberi; Eva M. Nielsen; Emily Kay; Clarence C. Tam; Craig D. Higgins; Laura C. Rodrigues; Judith F. Richardson; Sarah J. O'Brien; Brendan W. Wren (Environmental Microbiology, 2013)
Summary C ampylobacter jejuni is the leading cause of human bacterial gastroenteritis worldwide, but source attribution of the organism is difficult. Previously, DNA microarrays were used to investigate isolate source, which suggested a non‐livestock source of infection. In this study we analysed the genome content of 162 clinical, livestock and water and wildlife ( WW ) associated isolates combined with the previous study. Isolates were grouped by genotypes into nine clusters ( C 1 to C 9). Multilocus sequence typing ( MLST ) data demonstrated that livestock associated clonal complexes dominated clusters C 1– C 6. The majority of WW isolates were present in the C 9 cluster. Analysis of previously reported genomic variable regions demonstrated that these regions were linked to specific clusters. Two novel variable regions were identified. A six gene multiplex PCR ( mPCR ) assay, designed to effectively differentiated strains into clusters, was validated with 30 isolates. A further five WW isolates were tested by m PCR and were assigned to the C 7‐ C 9 group of clusters. The predictive mPCR test could be used to indicate if a clinical case has come from domesticated or WW sources. Our findings provide further evidence that WW C . jejuni subtypes show niche adaptation and may be important in causing human infection.

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Sequence Analysis of 5′ Regulatory Regions of the Machado–Joseph Disease Gene (ATXN3) - Conceição Bettencourt; Mafalda Raposo; Nadiya Kazachkova; Cristina Santos; Teresa Kay; João Vasconcelos; Patrícia Maciel; Karina C. Donis; Maria Luiza Saraiva-Pereira; Laura B. Jardim; Jorge Sequeiros; Jácome Bruges-Armas; et al. (The Cerebellum, 2012)

Cone morphologies associated with shallow marine eruptions: east Pico Island, Azores - Neil C. Mitchell; Rachelle Stretch; Clive Oppenheimer; Daniel Kay; Christoph Beier (Bulletin of Volcanology, 2012)

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

Folate and vitamin B12-related genes and risk for omphalocele - James L. Mills; Tonia C. Carter; Denise M. Kay; Marilyn L. Browne; Lawrence C. Brody; Aiyi Liu; Paul A. Romitti; Michele Caggana; Charlotte M. Druschel (Human Genetics, 2012)

Development of regional future climate change scenarios in South America using the Eta CPTEC/HadCM3 climate change projections: climatology and regional analyses for the Amazon, São Francisco and the Paraná River basins - Jose A. Marengo; Sin Chan Chou; Gillian Kay; Lincoln M. Alves; José F. Pesquero; Wagner R. Soares; Daniel C. Santos; André A. Lyra; Gustavo Sueiro; Richard Betts; Diego J. Chagas; Jorge L. Gomes; et al. (Climate Dynamics, 2012)

The Arctic’s rapidly shrinking sea ice cover: a research synthesis - Julienne C. Stroeve; Mark C. Serreze; Marika M. Holland; Jennifer E. Kay; James Malanik; Andrew P. Barrett (Climatic Change, 2012)

Society, demography and genetic structure in the spotted hyena - KAY E. HOLEKAMP; JENNIFER E. SMITH; CHRISTOPHER C. STRELIOFF; RUSSELL C. VAN HORN; HEATHER E. WATTS (Molecular Ecology, 2012)
Spotted hyenas ( Crocuta crocuta ) are large mammalian carnivores, but their societies, called ‘clans’, resemble those of such cercopithecine primates as baboons and macaques with respect to their size, hierarchical structure, and frequency of social interaction among both kin and unrelated group‐mates. However, in contrast to cercopithecine primates, spotted hyenas regularly hunt antelope and compete with group‐mates for access to kills, which are extremely rich food sources, but also rare and ephemeral. This unique occurrence of baboon‐like sociality among top‐level predators has favoured the evolution of many unusual traits in this species. We briefly review the relevant socio‐ecology of spotted hyenas, document great demographic variation but little variation in social structure across the species’ range, and describe the long‐term fitness consequences of rank‐related variation in resource access among clan‐mates. We then summarize patterns of genetic relatedness within and between clans, including some from a population that had recently gone through a population bottleneck, and consider the roles of sexually dimorphic dispersal and female mate choice in the generation of these patterns. Finally, we apply social network theory under varying regimes of resource availability to analyse the effects of kinship on the stability of social relationships among members of one large hyena clan in Kenya. Although social bonds among both kin and non‐kin are weakest when resource competition is most intense, hyenas sustain strong social relationships with kin year‐round, despite constraints imposed by resource limitation. Our analyses suggest that selection might act on both individuals and matrilineal kin groups within clans containing multiple matrilines.

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Menopausal hormone therapy and risk of ovarian cancer in the European prospective investigation into cancer and nutrition - Konstantinos K. Tsilidis; Naomi E. Allen; Timothy J. Key; Laure Dossus; Rudolf Kaaks; Kjersti Bakken; Eiliv Lund; Agnès Fournier; Christina C. Dahm; Kim Overvad; Louise Hansen; Anne Tjønneland; et al. (Cancer Causes & Control, 2011)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

The geochemistry of a dying continental arc: the Incapillo Caldera and Dome Complex of the southernmost Central Andean Volcanic Zone (~28°S) - A. R. Goss; S. M. Kay; C. Mpodozis (Contributions to Mineralogy and Petrology, 2011)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Passerine Exposure to Primarily PCDFs and PCDDs in the River Floodplains Near Midland, Michigan, USA - Timothy B. Fredricks; Matthew J. Zwiernik; Rita M. Seston; Sarah J. Coefield; Stephanie C. Plautz; Dustin L. Tazelaar; Melissa S. Shotwell; Patrick W. Bradley; Denise P. Kay; John P. Giesy (Archives of Environmental Contamination and Toxicology, 2010)

Nutrition and interference competition have interactive effects on the behavior and performance of Argentine ants - Adam D. Kay; Taylor Zumbusch; Justa L. Heinen; Tom C. Marsh; David A. Holway (Ecology, 2010)
Food availability often influences competitive outcomes through effects on consumer growth. Although it has received less attention, food availability may also affect competition through nutritional effects on behavior. One hypothesis linking nutrition and competition in ants posits that increased access to carbohydrates favors greater investment in worker traits that underlie behavioral dominance. We tested this hypothesis by varying dietary protein : carbohydrate (P:C) ratios and levels of interspecific interference for Argentine ants ( Linepithema humile ), a widespread invasive species. As predicted, colonies facing interference increased patrolling more when reared on low P:C diets; this result is the first demonstration of an interactive effect of nutrition and interference on ant colonies. Several results suggest that this dietary effect on patrolling was due primarily to changes in colony size rather than worker behavior. Colonies on lower P:C diets had lower worker mortality and larger final colony sizes. Diet had little effect on per capita patrolling, and worker behavior in performance assays depended more on previous exposure to interference than on diet. Our findings indicate that dietary P:C ratios can influence Argentine ant performance in a competitive environment and suggest a mechanism by which monopolization of carbohydrate‐rich resources can help invasive ants displace native ant competitors.

Presence and metabolism of endogenous androgenic–anabolic steroid hormones in meat-producing animals: a review - J. Scarth; C. Akre; L. van Ginkel; B. Le Bizec; H. De Brabander; W. Korth; J. Points; P. Teale; J. Kay (Food Additives & Contaminants: Part A, 2009)

Hypoxia and cardiac arrhythmias in breath-hold divers during voluntary immersed breath-holds - Jochen Hansel; Isabelle Solleder; Wilfried Gfroerer; Claus M. Muth; Klaus Paulat; Perikles Simon; Hans-C. Heitkamp; Andreas Niess; Kay Tetzlaff (European Journal of Applied Physiology, 2009)

Impact of expert versus measurement-based occupational noise exposure estimates on exposure-response relationships - Melissa C. Friesen; Hugh W. Davies; Aleck Ostry; Kay Teschke; Paul A. Demers (International Archives of Occupational and Environmental Health, 2008)

Contrasting levels of genetic differentiation among putative neutral microsatellite loci in Atlantic herring Clupea harengus populations and the implications for assessing stock structure - Phillip C. Watts; David O’Leary; Mary C. Cross; Jamie Coughlan; Eileen Dillane; Suzanne M. Kay; Suzanne Wylde; René Stet; Richard D. M. Nash; Emma M. C. Hatfield; Thomas F. Cross (Hydrobiologia, 2008)

Analysis of skeletal muscle function in the C57BL6/SV129 syncoilin knockout mouse - Karl J. A. McCullagh; Ben Edwards; Matthew W. Kemp; Laura C. Giles; Matthew Burgess; Kay E. Davies (Mammalian Genome, 2008)

Exploring gene-environment interactions in Parkinson’s disease - Colin C. McCulloch; Denise M. Kay; Stewart A. Factor; Ali Samii; John G. Nutt; Donald S. Higgins; Alida Griffith; John W. Roberts; Berta C. Leis; Jennifer S. Montimurro; Cyrus P. Zabetian; Haydeh Payami (Human Genetics, 2008)

Rehabilitation of Swamp Paperbark (Melaleuca ericifolia) wetlands in south-eastern Australia: effects of hydrology, microtopography, plant age and planting technique on the success of community-based revegetation trials - Elisa J. Raulings; Paul I. Boon; Paul C. Bailey; Michael C. Roache; Kay Morris; Randall Robinson (Wetlands Ecology and Management, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

Distinguishing the noise and attractor strength of coordinated limb movements using recurrence analysis - Michael J. Richardson; R. C. Schmidt; Bruce A. Kay (Biological Cybernetics, 2007)

Effects of plant harvesting and nutrient enrichment on phytoplankton community structure in a shallow urban lake - Kay Morris; Paul C. E. Bailey; Paul I. Boon; Leesa Hughes (Hydrobiologia, 2006)

Cancer and Occupational Exposure to Pentachlorophenol and Tetrachlorophenol (Canada) - Paul A. Demers; Hugh W. Davies; Melissa C. Friesen; Clyde Hertzman; Aleck Ostry; Ruth Hershler; Kay Teschke (Cancer Causes & Control, 2006)

Development of Ligament-Like Structural Organization and Properties in Cell-Seeded Collagen Scaffolds in vitro - Eileen Gentleman; Glen A. Livesay; Kay C Dee; Eric A. Nauman (Annals of Biomedical Engineering, 2006)

C-peptide, IGF-I, sex-steroid hormones and adiposity: a cross-sectional study in healthy women within the European Prospective Investigation into Cancer and Nutrition (EPIC) - Irene D. Bezemer; Sabina Rinaldi; Laure Dossus; Carla H. van. Gils; Petra H. M. Peeters; Paulus A. H. van. Noord; H. Bas Bueno-de-Mesquita; Soren Paaske Johnsen; Kim Overvad; Anja Olsen; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2005)

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

Development and Characterization of a Nonmorphogenetic Cell Line of Wheat (Triticum aestivum) - Arron C. Guenzi; Kay Scheets; J. Larry Green; John P. Fellers (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Behavioural structuring of relatedness in the spotted hyena ( Crocuta crocuta ) suggests direct fitness benefits of clan‐level cooperation - Russell C. Van Horn; Anne L. Engh; Kim T. Scribner; Stephan M. Funk; Kay E. Holekamp (Molecular Ecology, 2004)
Spotted hyenas ( Crocuta crocuta ) are gregarious carnivores that live in multigenerational social groups, called clans, containing one to several matrilines. Members of multiple matrilines within a clan cooperate during dangerous interactions with inter‐ and intraspecific competitors. The evolution of cooperation may be influenced by relatedness between individuals, which in turn is influenced by reproductive skew and mate choice, dispersal and territorial behaviours. Behavioural data exist for spotted hyenas, but corresponding data on patterns of relatedness are unavailable; this lack of data makes it difficult to assess the relative importance of selection pressures favouring cooperative behaviour within and among groups. Therefore we conducted a longitudinal analysis of relatedness within a single large clan of spotted hyenas, as well as a cross‐sectional analysis of relatedness among hyenas from multiple clans. Within a clan, patterns of relatedness reflected known pedigree relationships, and relatedness was higher within than among matrilines, even across generations. Although mean within‐matriline relatedness varied among matrilines, it did not decline with matriline rank. On average, clan members were not related closely, due to high levels of male‐mediated gene flow among clans, and relatedness declined very slightly across clan borders. Low mean relatedness within clans suggests that spotted hyenas cooperate with unrelated clan‐mates against close paternal kin in other clans. Our data also suggest that spotted hyenas must derive large net direct fitness benefits from group living and cooperation.

A Device for Long Term, In Vitro Loading of Three-Dimensional Natural and Engineered Tissues - Daniel A. Shimko; Kyle K. White; Eric A. Nauman; Kay C Dee (Annals of Biomedical Engineering, 2003)

Risk factors for failure to detect a cancer during clinical breast examinations (United States) - Janet Kay Bobo; Herschel W. Lawson; Nancy C. Lee (Cancer Causes & Control, 2003)

Research Report: Learning Styles of Biomedical Engineering Students - Kay C Dee; Eric A. Nauman; Glen A. Livesay; Janet Rice (Annals of Biomedical Engineering, 2002)

A comprehensive worksite cancer prevention intervention: behavior change results from a randomized controlled trial (United States) - Glorian Sorensen; Anne M Stoddard; Anthony D. LaMontagne; Karen Emmons; Mary Kay Hunt; Richard Youngstrom; Deborah McLellan; David C Christiani (Cancer Causes & Control, 2002)

Genetic mapping of eight SH3 domain genes on seven mouse chromosomes - Chun G. Lee; Herbert C. Morse III; Brian K. Kay; Christine A. Kozak (Mammalian Genome, 1999)

Axial Vibration of Threaded External Fixation Pins: Detection of Pin Loosening - Matthew W. Kay; Simon C. Roe; Larry F. Stikeleather; Azza Mahmoud; C. Frank Abrams, Jr. (Annals of Biomedical Engineering, 1998)